Synthesis Process and Properties of V5+-Doped LiFePO4/C - Shao, Zongping; Xia, J.; Liu, X.; Li, G. (Springer, 2016)
Olivine structure LiFe1−xVxPO4/C (x = 0.02, 0.04, 0.06) composite materials as the cathode for lithium ion batteries were synthesized by carbon-thermal reduction method, using Fe(NO3)3 · 9H2O, LiH2PO4, NH4VO3, and C6H12O6 (glucose) as raw materials. The X-ray diffraction (XRD), scanning electronic microscope (SEM) laser particle size analysis, specific surface area tester, and electrochemical performance testing were used to study its structure, morphology, and electrochemical properties. The results showed that the diffraction peaks of the prepared materials correspond to the single phase of LiFePO4/C and can be indexed as the olivine structure. Particle diameter of LiFe1−xVxPO4/C (x = 0.04) was uniform. Specific surface areas of materials are all increased. An electrochemical test showed that LiFe1−xVxPO4/C (x = 0.04) demonstrated a better electrochemical capacity of 141.065 mAh · g−1 at 0.1C rate, and which had an increase of 10.77% than the un-doped sample. After 20 cycles, charge and discharge specific capacity almost had no attenuation.